THE NATURE OF THE TYPE C SEMI-REGULAR VARIABLES - Turner, D. G. (Одеські астрономічні публікації, 2017)
The type C semi-regular (SRC) variables are M-type supergiants like Betelgeuse that undergo regular periodic brightness fluctuations superposed upon seemingly irregular trends. Many of the 55 recognized Milky Way M-type supergiants belonging to the class are multi-periodic, with radial pulsation almost certainly the source of their primary short-period luminosity changes. Noted here are additional characteristics of the stars, not supplied in the GCVS, that can be recognized in their growing archival inventories: amplitude for both long-term and short-term light variability increasing with luminosity, regular changes in mean brightness possibly tied to evolution, and a period-luminosity relation in need of further observational corroboration. As the immediate stellar precursors to many Type II supernovae and as auxiliary standard candles for the extragalactic distance scale, SRC variables are in need of more extensive observational studies to elucidate their many intriguing properties.